Heterogeneous Fenton reactants: a study of the behavior of iron oxide nanoparticles obtained by the polymeric precursor method - Giraldi, Tania R. [UNESP]; Arruda, Cezar C.; da Costa, Geraldo M.; Longo, Elson [UNESP]; Ribeiro, Caue (Springer, 2009)
Nanoparticles composed of iron oxides and iron salts were obtained from polymeric resins produced by polymerizing Fe(2+)-citrate and Fe(3+)-citrate complexes with ethylene glycol. The citric acid:Fe molar ratio was varied to obtain different synthesis conditions. The materials were treated at 450 degrees C for 2 h to obtain nanoparticles, which were characterized by XRD, Mossbauer spectroscopy, FEG, CHNS, atomic absorption and surface area through N(2) physisorption. Rhodamine B photo degradation in the presence of these nanoparticles and hydrogen peroxide was carried out to analyze the possible behavior of nanoparticles as heterogeneous Fenton reactants. UV-visible spectroscopy revealed that the catalytic activity in the presence of nanoparticles obtained with a citric acid:Fe molar ratio of 12:1 was the condition that provided the best results in this work.
Keywords: Photodegradation; Dye; Water treatment; Ferrites; Polymeric precursors